2019
DOI: 10.1002/jcla.23079
|View full text |Cite
|
Sign up to set email alerts
|

The effects of DICER1 and DROSHA polymorphisms on susceptibility to recurrent spontaneous abortion

Abstract: Background Recurrent spontaneous abortion (RSA) is a serious problem in pregnancy. The exact etiology of RSA is unknown in more than 50% of all the patients. However, genetic variations are known as susceptibility factors for idiopathic RSA. Considering the role of miRNA biosynthesis machinery in the miRNA production and effect of miRNAs on various diseases, this study aimed to evaluate the effects of DICER1 rs3742330 and DROSHA rs6877842 polymorphisms on RSA risk. Methods In this case‐control study, 150 RSA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…DICER1 is essential for the synthesis and biogenesis of miRNAs [36]. Though we identified a de novo frameshift SNV in stillbirth, other polymorphisms in DICER1 were previously shown to be associated with spontaneous miscarriage before 20 weeks' gestation [45] and recurrent pregnancy loss before 14 weeks' gestation [46]. Suggested mechanisms of DICER1 include decidualization of endometrial stroma, which are critical trophoblast invasion and placental function [25,46,47].…”
Section: Plos Onementioning
confidence: 86%
“…DICER1 is essential for the synthesis and biogenesis of miRNAs [36]. Though we identified a de novo frameshift SNV in stillbirth, other polymorphisms in DICER1 were previously shown to be associated with spontaneous miscarriage before 20 weeks' gestation [45] and recurrent pregnancy loss before 14 weeks' gestation [46]. Suggested mechanisms of DICER1 include decidualization of endometrial stroma, which are critical trophoblast invasion and placental function [25,46,47].…”
Section: Plos Onementioning
confidence: 86%
“…From the genetic susceptibility point of view, some studies identified an association between Drosha and/or Dicer polymorphisms and the risk of endometriosis ( 33 ) and recurrent spontaneous abortion ( 34 ), conditions known to be associated with adenomyosis ( 35 ). Another hypothesis - although it is not safe to use it to explain the variation in the expression of these proteins in adenomyosis specimens - is the involvement of proteins p53, p63, and p73.…”
Section: Discussionmentioning
confidence: 99%
“…The study group consisted of 161 women with idiopathic IRSM, who presented with a history of at least two consecutive pregnancy losses at less than 20 weeks of gestation and 177 healthy women as controls. The enrollment procedure has been described in our previous work [ 29 ]. The local Ethics Committee of Zahedan University of Medical Sciences approved the study (IR.ZAUMS.REC.1399.093).…”
Section: Methodsmentioning
confidence: 99%